Novel method to estimate the length of palmaris longus tendon - Arumugam, Manohar; Gyanchand Rampal, Lekhraj Rampal (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
Palmaris longus is tendon of choice in reconstructive, plastic and cosmetic surgeries. Thus, a suitable length is required and it would be more convenient if the length of the tendon of the palmaris longus could be estimated before harvesting. This study was carried out to determine the relationship between the length and width of the palmaris longus tendon and the length of forearm and hand, the relationship between the length and the width of the palmaris longus tendon and wrist width and wrist circumference, as well as to identify a technique to estimate the length of the tendinous part of palmaris longus before harvesting it. A standardized proforma was used to collect the data of each of the 31 cadavers upper limbs. These data were analysed using SPSS software version 17. It is important to note that p value less than 0.05 is considered as statistically significant in this study. Out of the 31 upper limbs, palmaris longus tendon was absent in 3 (9.68%). Meanwhile, the mean length and width of the palmaris longus tendon was found to be 16.20 cm and 0.48 cm, respectively. The mean length of the forearm and hand was 26.6 cm and 21.2 cm, respectively. The mean width of the wrist and wrist circumference was 8.2 cm and 14.82 cm, respectively. These indicate a significant and moderate relationship between the length of palmaris longus tendon and the length of forearm (r = 0.49, r2=0.24, p < 0.01). In addition, there was also a significant relationship between the length of palmaris longus tendon and the length of hand (r = 0.56, p < 0.01). This paper presents the technique used to estimate the length and width of the tendinous part of palmaris longus before harvesting. The length of palmaris longus can be estimated pre-operatively by measuring the length of the hand by using the technique explained in this paper.